The genetics of congenital heart disease… understanding and improving long-term outcomes in congenital heart disease: a review for the general cardiologist and primary care physician. Issue 5 (October 2017) - Simmons, M. Abigail; Brueckner, Martina
Abstract : Purpose of review: This review has two purposes: to provide an updated review of the genetic causes of congenital heart disease (CHD) and the clinical implications of these genetic mutations, and to provide a clinical algorithm for clinicians considering a genetics evaluation of a CHD patient. Recent findings: A large portion of congenital heart disease is thought to have a significant genetic contribution, and at this time a genetic cause can be identified in approximately 35% of patients. Through the advances made possible by next generation sequencing, many of the comorbidities that are frequently seen in patients with genetic congenital heart disease patients can be attributed to the genetic mutation that caused the congenital heart disease. These comorbidities are both cardiac and noncardiac and include: neurodevelopmental disability, pulmonary disease, heart failure, renal dysfunction, arrhythmia and an increased risk of malignancy. Identification of the genetic cause of congenital heart disease helps reduce patient morbidity and mortality by improving preventive and early intervention therapies to address these comorbidities. Summary: Through an understanding of the clinical implications of the genetic underpinning of congenital heart disease, clinicians can provide care tailored to an individual patient and continue to improve the outcomes of congenital heart disease patients.